Problematika Penyandang Disabilitas Dalam Pemilu Studi Kasus Pemilu Legislatif Tahun 2014 di Jakarta - Kharima, Nadya (Social Welfare Study Program, 2016)
General election, as a locust for citizens, functions to practice their voting rights, including those people with different abilities. Although there have been policies covering the right of the later, until now, the election system still facing problems for fulfilling the right for people with disabilities. Based on report documents of two general elections, this article discusses several crucial challenges such as data on people with disabilities, accessibility to voting venue, lack of understanding of both field officer and persons with disabilities. Thus, these situations reflect a big agenda for the expected future elections in regard to in the fulfillment of persons with disabilities rights.Keywords: Penyandang Disabilitas, Pemilu, Aksebilitas.